2019
DOI: 10.3390/f10050423
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Alleviated Salt Damage of Populus euphratica: A Physiological and Transcriptomic Analysis

Abstract: Populus euphratica Oliv. is a model tree for studying abiotic stress, especially salt stress response. Salt stress is one of the most extensive abiotic stresses, which has an adverse effect on plant growth and development. Salicylic acid (SA) is an important signaling molecule that plays an important role in modulating the plant responses to abiotic stresses. To answer whether the endogenous SA can be induced by salt stress, and whether SA effectively alleviates the negative effects of salt on poplar growth is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…On the other hand, enzymatic antioxidants (e.g., catalase, peroxidase, and superoxide dismutase) and non-enzymatic antioxidants (ascorbic acid and carotene) are accumulated under various stresses to deal with the increase of ROS and protect the plant tissues from oxidative damage under various stresses [ 17 , 18 ]. Therefore, plants need several strategies to overcome the detrimental effects of salt stress through osmotic adjustments and photosynthetic process improvements [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, enzymatic antioxidants (e.g., catalase, peroxidase, and superoxide dismutase) and non-enzymatic antioxidants (ascorbic acid and carotene) are accumulated under various stresses to deal with the increase of ROS and protect the plant tissues from oxidative damage under various stresses [ 17 , 18 ]. Therefore, plants need several strategies to overcome the detrimental effects of salt stress through osmotic adjustments and photosynthetic process improvements [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a stress tolerance inducer and an important signal in many physiological processes, such as proline metabolism and photosynthesis. It reduces oxidative stress in plants under environmental stress and enhances plant growth and productivity under salt- [17] and drought-stress conditions [18]. Foliar application of SA-enhanced growth characteristics of sweet pepper plants [6] has increased the chlorophyll concentrations and enzyme activitives in barley plants, as well as counteracting the deleterious impacts of salinity on faba beans [19].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical treatments can also improve salt tolerance. Here, Rao et al [20] showed that pre-exposure of Populus euphratica to salicylic acid (0.4 mM) enhanced the performance of plants under subsequent massive salt stress (300 mM). The beneficial effect was concentration dependent and disappeared in plants exposed to 1 mM salicylic acid.…”
Section: Salinity and Combined Stresses: From Soil Amendment To Redoxmentioning
confidence: 97%